2009
DOI: 10.1097/aci.0b013e32831d8184
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and treatment for obstructive sleep apnea amongst obese children and adults

Abstract: In view of recent findings, a direct association between body mass and upper airway obstruction should be viewed with caution. Obesity may play a more significant role in the predisposition to OSA amongst particular subgroups of the population, such as adults, and those with particular craniofacial and upper airway morphology. Healthcare prioritization and requirements may be more substantial for such groups. Further, commonly used treatment methods for OSA (such as adenotonsillectomy for children and continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 76 publications
1
15
0
1
Order By: Relevance
“…We obtained a proportion of normal results in 66 patients (34%), revealing a large number of unnecessary exams that are performed every day in Vila Nova de Gaia/Espinho hospital center, with the possibility of this result being generalized to the different hospital centers in the country. Male gender was more prevalent (63%), agreeing with the literature [1,10,16,[20][21][22]27,30,36,[42][43][44][45]. Possible explanations are the higher prevalence of craniofacial and upperairway abnormalities (21%), and also snoring (90%).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We obtained a proportion of normal results in 66 patients (34%), revealing a large number of unnecessary exams that are performed every day in Vila Nova de Gaia/Espinho hospital center, with the possibility of this result being generalized to the different hospital centers in the country. Male gender was more prevalent (63%), agreeing with the literature [1,10,16,[20][21][22]27,30,36,[42][43][44][45]. Possible explanations are the higher prevalence of craniofacial and upperairway abnormalities (21%), and also snoring (90%).…”
Section: Discussionsupporting
confidence: 80%
“…Recommendations from the American Academy of Sleep Medicine state that OSA is present when AHI ≥ 5. It can be classified as mild (AHI: 5-15), moderate (AHI: [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], or severe (AHI ≥ 30) [6,7,13,22]. Approximately 30% of the general public is affected by a significant sleep problem, often of long standing [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several hypotheses also have been proposed for explaining why obese children are at risk of SDB, including reduction of the intrathoracic volume causing lower oxygen reserves [29], impaired ventilatory responses to hypoxia and hypercapnia, hypoventilation because of leptin resistance [30], and central apnea followed by narrowing or collapse of the upper airway [31]. In practice, an important concern is that obese children may have adenotonsillar hypertrophy [32,33], which may reduce the cross-sectional diameter of the upper airway [34]. However, the effect of adenotonsillar hypertrophy was not evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that snoring is independently associated with an elevated risk for type 2 diabetes. Obesity, age, and menopause are known risk factors for OSA [20]. In the AHEAD study [12], waist circumference is found to be the only significant predictor of the presence of OSA (AHI≥5) in diabetics.…”
Section: Resultsmentioning
confidence: 99%